Resilience of Muslim Identity in Singapore: Muslims under the Challenges and Impacts of Globalization in Post-Independence Singapore 1965-2017 - Darmawan, Budi; Nelmawarni, Nelmawarni; Erman, Erman (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2024)
This research probes the ramifications of globalization on Muslim identity in Singapore since its independence in 1965, concentrating on the four economic development phases pivotal to the nation's growth. It concurrently traces the post-independence evolution of Muslim life, specifically in religious practices and social norms. Singapore's globalization-driven economic ascent, its status as a developed nation, and its competitive business environment stand as evident outcomes. However, the Muslim communities grapple with the challenge of adapting to global shifts while preserving their Islamic identity. The study emphasizes the imperative of comprehending the intricate interplay between globalization and Muslim identity in Singapore. Employing the historical method comprising heuristics, criticism, interpretation, and historiography, the research analyzes historical records and relics. Findings underscore the instrumental role of technology and social media in shaping Muslim identity, facilitating the dissemination of religious information and fostering global connectivity within Muslim communities. While the Singapore government's multiculturalism policy aims for interfaith harmony and recognizes the Muslim community's integral role, restrictions on public expressions of religious identity reflect the state's secular stance. This research offers a profound understanding of the complex dynamics between globalization and Muslim identity in Singapore, shedding light on the challenges and opportunities encountered by Muslim communities in safeguarding their cultural and religious diversity amidst the ever-evolving global landscape.